Silymarin Ameliorates Oxidative Stress and Enhances Antioxidant Defense System Capacity in Cadmium-Treated Mice - Farjad, Elham (Cell J, 2018)
OBJECTIVE: Cadmium is an environmental pollutant which induces oxidative stress while silymarin as an antioxidant is able to scavenge free radicals. The aim of the present study was to investigate the effect of silymarin on oxidative stress markers and antioxidant defense system capacity in mice treated with cadmium chloride. MATERIALS AND METHODS: In this experimental study, adult mice were divided into four groups as follow: i. Control, ii. Cadmium chloride (5 mg/kg b.w., s.c.), iii. Silymarin+cadmium chloride, and iv. Silymarin (100 mg/kg b.w., i.p.). Mice were treated with cadmium chloride for 24 hours and silymarin was administered 24 hours before the cadmium. Blood samples were then collected from the experimental groups and their sera were prepared. To investigate oxidative stress markers in the serum, the amount of malondialdehyde (MDA) and thiol groups (-SH) were evaluated. To measure the total antioxidant power in the serum, Ferric Reducing/ Antioxidant Power (FRAP) method was used. In addition, the activity of enzymes including catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) was assessed to evaluate serum antioxidant defense power. RESULTS: In the cadmium-treated group, the amount of MDA significantly increased as compared to the control group. In silymarin+cadmium group, silymarin significantly ameliorated the level of MDA compared to the cadmium group. In addition, cadmium significantly reduced serum FRAP, the activity of antioxidant defense system enzymes and thiol groups compared to the control. In silymarin+cadmium group, silymarin could significantly reverse the reduction of these markers compared to the cadmium group. Administration of silymarin alone caused a significant increase in serum FRAP, the activity of antioxidant defense system enzymes and thiol groups compared to the control group. CONCLUSION: Silymarin as a powerful antioxidant reverses the toxic effect of cadmium on the serum levels of lipid peroxidation, total antioxidant power, antioxidant defense system enzymes activity and thiol groups.